GAMBARAN CEMARAN Escherichia coli PADA DAGING AYAM BROILER DI PASAR TRADISIONAL SINGARAJA - Made Raningsih; Putu Wahyu Sri Juniantari Sandy (STIKes Buleleng, 2018)
Introduction: The nutrients contained in meat must be maintained, one of them are by paying attention to hygienic requirements, sanitation of business unit facilities so that the product produced are safe to consumption. Therefore, it is necessary to conduct laboratory testing to ensure the food from the animal is free from harmful microorganisms. Coliform bacteria, one of which is Escherichia coli in chicken meat, is one indicator of the level of sanitation in food products derived from animals. Method: this research is a descriptive observational quantitative research with cross sectional approach and laboratory to examinante the amount of Escherichia coli contamination in chicken meat was sold in traditional markets in Singaraja town. The total sample are 17. The results: based on the results of the study from 17 samples it founded are 2 samples had E.coli contamination> 101 cfu / g, 5 samples <101 cfu / g, and 10 samples are negative. Conclusion: Based on the results of the study it can be concluded that the presence of E. Coli contamination is overcomes the SNI limit can be caused by environmental factors and packaging by traders.